Cinaciguat Prevents Postnatal Closure of Ductus Arteriosus by Vasodilation and Anti-remodeling in Neonatal Rats - Hung, Yu-Chi; Liu, Yi-Ching; Wu, Bin-Nan; Yeh, Jwu-Lai; Hsu, Jong-Hau (Frontiers in Physiology, 2021)
Closure of the ductus arteriosus (DA) involves vasoconstriction and vascular remodeling. Cinaciguat, a soluble guanylyl cyclase (sGC) activator, was reported with vasodilatory and anti-remodeling effects on pulmonary hypertensive vessels. However, its effects on DA are not understood. Therefore, we investigated whether cinaciguat regulated DA patency and examined its underlying mechanisms. In vivo, we found that cinaciguat (10 mg/kg, i.p. at birth) prevented DA closure at 2 h after birth with luminal patency and attenuated intimal thickening. These anti-remodeling effects were associated with enhanced expression of cyclic guanosine monophosphate (cGMP) in DA. Ex vivo, cinaciguat dilated oxygen-induced DA constriction dose-dependently. Such vasodilatory effect was blunted by KT-5823, a PKG inhibitor. In DA smooth muscle cells (DASMCs), we further showed that cinaciguat inhibited angiotensin II (Ang II)-induced proliferation and migration of DASMCs. In addition, cinaciguat inhibited Ang II-induced mitochondrial reactive oxygen species (ROS) production. Finally, Ang II-activated MAPKs and Akt were also inhibited by cinaciguat. In conclusion, cinaciguat prevents postnatal DA closure by vasodilation and anti-remodeling through the cGMP/PKG pathway. The mechanisms underlying anti-remodeling effects include anti-proliferation and anti-migration, with attenuation of mitochondrial ROS production, MAPKs, and Akt signaling. Thus, this study implicates that sGC activation may be a promising novel strategy to regulate DA patency.